Measuring outcomes in trials of interventions for people who self-harm: qualitative study of service users' views. Issue 2 (March 2020) - Owens, Christabel; Fox, Fiona; Redwood, Sabi; Davies, Rosemary; Foote, Lisa; Salisbury, Naomi; Williams, Salena; Biddle, Lucy; Thomas, Kyla
Abstract : Background: Patients often have very different ideas from clinicians about what they want treatments to achieve. Their views on what outcomes are important are not always reflected in trials. Aims: To elicit the views of people who self-harm on the most commonly used outcome measures and to identify the outcomes that matter to them. Method: We conducted in-depth interviews with 18 people with histories of self-harm, recruited from hospital and community settings. We conducted thematic analysis using a framework approach and used visual mapping to arrive at our final analysis and interpretation. Results: Participants' accounts contained a number of challenges to the validity and meaningfulness of current trial outcome measures. Five broad issues emerged: (a) relationship between frequency and severity of self-harm; (b) behavioural substitution; (b) self-management skills; (d) the role of self-harm as survival tool and affect regulator, and (e) strategic self-presentation. We show how these affect the visibility and measurability of commonly used outcomes. The outcomes that mattered to participants focused on positive achievements in three domains: (a) general functioning and activities of everyday living; (b) social participation, and (c) engagement with services. Participants conceptualised these as both measures and means of sustained improvement. Conclusions: Our findings suggest that current self-harm trial science rests on flawed assumptions about the relationship between mental states and behaviours and about our ability to measure both. Greater understanding of the outcomes that matter to people who self-harm is needed to inform both intervention development and trial design.